Carbon emission quantification and decarbonization policy exploration for the household sector - Evidence from 51 Japanese cities. (May 2020) - Jiang, Yida; Long, Yin; Liu, Qiaoling; Dowaki, Kiyoshi; Ihara, Tomohiko
Abstract: The household sector has been identified as a major driver of the economy and an important contributor to greenhouse gas (GHG) emissions. It is also pointed out by existing studies that influential factors of household emissions range from socioeconomic to geographic aspects. Promoting efficient and feasible decarbonization actions therefore calls for the quantification of the variability in emission patterns and its relationship with contextual factors. In this study, using data on monthly household expenditures at the city level, direct and indirect carbon emissions resulting from household consumption in 51 major Japanese cities in 2011 are calculated. A regression analysis is also conducted to explore the relationship between emissions from the household sector and the socioeconomic, demographic, and climatic characteristics of Japanese cities. Our results indicate seasonality and categorical differences in residential carbon emissions for cities in Japan. We also find per capita income, urban population density, and proportion of the population over 65 years old to be the most influential variables that shape the residential emission landscape of Japanese cities. We thus suggest that seasonality, categories of consumption, and city characteristics be considered as crucial factors in policy making for emission mitigation targeting consumption behavior of urban residents. Highlights: An estimation of city-level emissions from consumption is conducted for Japan. Data on monthly household expenditures are used for the estimation. Average GHG emissions are highest in December and lowest in June. Food and transportation lead to more emissions than other categories of consumption. Income, population density, and elderly ratio are influential in city-level emissions.